Can we rely on 'climate-friendly' consumption?. (August 2019) - Boström, Magnus; Klintman, Mikael
In policy and research on sustainable consumption in general, and climate-oriented consumption specifically, key questions centre around whether people are motivated and prompted to support such consumption. A common claim in the scholarly debate is that policy makers, in face of fundamental governance challenges, refrain from taking responsibility and instead invest unrealistic hopes in that consumers will solve pressing environmental problems through consumer choice. Although green consumption is challenging, specifically climate-friendly consumption is even more so, due to the particularly encompassing, complex and abstract sets of problems and since climate impact concerns the totality of one's consumption. Nevertheless, consumers are called to participate in the task to save the planet. This article draws on existing literature on climate-oriented consumption with the aim of contributing to a proper understanding of the relation between consumer action and climate mitigation. It provides a synthesis and presents key constraining mechanisms sorted under five themes: the value-action gap, individualisation of responsibility, knowledge gap, ethical fetishism and the rebound effect. This article concludes with a discussion of perspectives that endorse a socially embedded view of the citizen-consumer. The discussion indicates pathways for how to counteract the constraining mechanisms and open up room for climate-friendly citizen-consumers.